The Search For Local Government Autonomy In Nigeria: Legal And Institutional Pathways To Its Realization - Koni, Ifeolu J. (Journal of Sustainable Development Law and Policy, 2025)
This article examines the status of the local government under the tripartite governmental system in Nigeria that has been in operation since 1979. It reviews the various reforms that the administration of local government has gone through from the colonial era till 1999 when the extant Constitution of Nigeria came into force. The article finds that notwithstanding the provision of section 7 of the 1999 Constitution which provides for a system of local government by democratic means, many of the State Governments have continued to set up caretaker committees at this tier of government, thereby denying the grassroots population of the benefits of democratic rule. The creation of the infamous State Joint Local Government Account has rendered the Local Governments totally prostrate as they depend completely on the State Governments for funds needed for their development. The article recommends, inter alia, that section 165 of the 1999 Constitution should be amended with a view to abolishing the State Joint Local Government Account and making the Local Government Councils both politically and financially autonomous.